Number of Glia Cells in the Cerebrum and Cerebellum of Newborn Rats After Administration of Mackerel Fish Oil During Pregnancy - Nur Cholila; Widjiati Widjiati; Hermanto Tri Joewono (Universitas Muhammadiyah Semarang, 2024)
Omega 3 intake during pregnancy can support fetal brain growth and development. Omega 3 plays an important role in making neuron cell membranes and glia and protecting nerve cells. Mackerel is a source of omega 3 which is abundant and easily accessible to the people of Indonesia. The purpose of this study was to analyze the effect of mackerel oil intake on the number of glial cells (astrocytes, oligodendrocytes, and microglia) of the cerebrum and cerebellum of newborn rats. This research was a true experimental design with a post-test only control group. A total of 30 pregnant rats were randomized into 3 groups, namely the control group (K1), mackerel oil (K2), and omega 3 supplements (K3). Each group was given treatment on days 1-17 of pregnancy. On the 18th day, the termination was carried out. 3 newborn rats were taken from each parent and made preparations from brain tissue. Hematoxylin-Eosin test to assess the number of glial cells. The results showed the highest mean±SD number of glial cells (astrocytes, oligodendrocytes, and microglia) in the cerebrum and cerebellum was the highest in the mackerel oil group (174,460±33,777; 21,080±6,937; 11,300±2,090), and (156,280 ±34,980; 22,260±4,302; 11,060±2,383). ANOVA test showed a significant difference in the number of glial cells in the cerebrum and cerebellum between groups with a p-value <0.05. The results of this study can be concluded that the administration of mackerel oil during pregnancy can increase the number of glial cells (astrocytes, oligodendrocytes, and microglia) in the cerebrum and cerebellum of newborn rats.